Efficacy of ultrasonography-guided sterile isotonic saline aspirate in the isolation of microorganism in the management of cellulitis - Prabhakar, R.; Madhusudhan, Napa (International Surgery Journal, 2021)
Background: Cellulitis is an acute spreading infection of the skin and subcutaneous tissues characterized by local findings of tenderness, erythema, increased warmth, swelling, and regional adenopathy. Attempts to establish a precise bacteriologic diagnosis in most cases of cellulitis in adults are usually unrewarding, and therapy tends to be empiric. The aim of the study was to determine the efficacy of Ultrasonography guided sterile isotonic saline aspirate (UGSISA) in the isolation of microorganisms in the management of cellulitis. Methods: A cross-sectional study with 100 patients suffering from lower limb cellulitis was performed. The most infected area was marked with ultrasonography, using the 21 G needle under sterile precaution; around 0.5 ml of sterile isotonic saline was injected into the most infected area and aspirated. The aspirate was sent for gram staining, cultured, and analyzed according to standard procedures. Results: Needle aspirations in 100 patients were performed, and 30% had positive aspirants. The most common organism grown was Streptococci, and the least common was coagulase-negative Enterococcus, 2 patients had mixed infections. Major risk factors associated with lower limb cellulitis in our study were diabetes (54%) and spontaneous (20%). Conclusions: In our study, as a routine diagnostic procedure, needle aspiration may not be justified for all cellulitis patients, though it may still be useful in patients where the most infected area was marked with ultrasonography before needle aspiration.